TRAUMA SOSIAL DALAM HUBUNGAN INTERPERSONAL MAHASISWA : PERSPEKTIF TEORI PSIKOANALISIS SIGMUND FREUD - Fatimah, Siti; Nur Islami , Alin; Hamid , Naufal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Social trauma is a psychological experience arising from negative social interactions, which can significantly affect interpersonal relationships, particularly among university students in early adulthood. This study aims to analyze the forms, causes, and impacts of social trauma in students’ interpersonal relationships using the psychoanalytic perspective proposed by Sigmund Freud. This research employs a qualitative approach with a descriptive method, utilizing in-depth interviews and observations of students who exhibit indications of social trauma. The findings reveal that social trauma among students is commonly triggered by experiences such as rejection, bullying, interpersonal conflicts, and unhealthy relationships. From Freud’s psychoanalytic perspective, such trauma is associated with imbalances among the id, ego, and superego, resulting in the emergence of defense mechanisms, including repression, projection, and rationalization. The impacts include difficulties in building trust, a tendency toward social withdrawal, and disruptions in interpersonal communication. This study concludes that understanding individuals’ psychic dynamics through a psychoanalytic approach can help identify the root causes of social trauma and provide a foundation for more appropriate interventions within the context of students’ interpersonal relationships.